ANALISIS PENGARUH IPM, UPAH MINIMUM, DAN PDRB TERHADAP TINGKAT PENGANGGURAN KABUPATEN/KOTA DI PROVINSI BALI - Ambarini, Ni Kadek Dina; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700], 2022)
The purpose of this study was to analyze the effect of HDI. Simultaneously the Minimum Wage and GRDP on the Regency/City Unemployment Level in Bali Province, and analyze the effect of HDI. Minimum Wage and GRDP partially to Regency/City Unemployment level in Bali Province. The data used are secondary data, namely HDI, Minimum Wage, GRDP, and Regency/City Unemployment levels in Bali Province from 2015-2020 so that the number of observations is 54 observations. The analysis technique used is multiple linear regression analysis. The software used is Eviews. HDI, Minimum Wage, and GRDP simultaneously have a positive effect on the unemployment rate in districts/cities in the province of Bali. HDI partially does not have a positive and significant effect on the Regency/City unemployment rate in the Province of Bali. The Minimum Wage partially has a positive and significant effect on the Regency/City unemployment rate in the Province of Bali. PDRB partially does not have a positive and significant effect on the unemployment rate in the Regency/City in the Province of Bali.   Keywords: Unemployment, HDI, Minimum Wage, Gross Regional Domestic Product